PENGARUH KETEBALAN PEMAKANAN TERHADAP KEKASARAN PERMUKAAN PADA MATERIAL S45C - Budha Maryanti (University of Merdeka Malang, 2016)
Process that uses a CNC lathe is required to have the results of surface roughness (roughness) is small with a definite degree of roughness. To get the product that has a surface roughness as expected, can be influenced by several factors one of which is the thickness of the funeral. The purpose of this study to determine the extent of the influence of the thickness of the funeral to the surface roughness at S45C material. This research was carried out on the shaft material S45C specimens with diameter of 50 mm with a rotary speed of 1600 rpm using a CNC turning machine MT3040. Ingestion thickness variation using a 0.1 mm; 0.15 mm; 0.2 mm; 0.25 mm and 0.3 mm. Ingestion of motion while using only 0.15 mm / rotation by using a chisel insert VCMT 160 404 with a chisel tip radius of 0.4 mm. Results of research for the material S45C 50 mm diameter suitable parameter is the funeral 0.15 mm thick at 1600 rpm rotation produces minimum roughness Ry, Rmax = 11.76 ?m and 0.10 mm thick feeds at 1600 rpm rotation Ra = 2.67 ?m, and Rz = 11.03 lm. Meanwhile, if the funeral 0.30 mm thick and round 1400 rpm generate greater roughness is Ra = 3.65 ?m, Ry (Rmax) = 16.07 ?m and Rz = 13.28 lm